2019
DOI: 10.21203/rs.2.11771/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causes for diarrhoea and infection with intestinal parasites among HIV positive patients at a referral hospital in Central Ethiopia

Abstract: Background: Intestinal parasitic infections are a major public health challenge in many tropical countries.Opportunistic intestinal coccidia such as Cryptosporidia, Cytoisospora or Cyclospora species are common pathogens which are regularly missed using widely practiced wet mount stool microscopy techniques. Therefore, treatment choices are limited and mostly rely on empirical use of cotrimoxazole.The aim of this study was to determine the prevalence of intestinal parasitosis among HIV-infected individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this study, 22 cross-sectional articles were reported from one city administration and six regions of Ethiopia. Eight studies conducted in Amhara regional state [4,17,18,[30][31][32][33][34], six studies were done in Oromia regional state [28,[35][36][37][38][39], four studies conducted in South Nations, Nationalities and Peoples Regional state (SNNPR) [5,29,40,41], two articles reported from Tigray regional state [16,21], one study reported from Harari regional state [19] and one study was conducted in Oromia region, Afar region and Dire Dawa city administration [42] (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 22 cross-sectional articles were reported from one city administration and six regions of Ethiopia. Eight studies conducted in Amhara regional state [4,17,18,[30][31][32][33][34], six studies were done in Oromia regional state [28,[35][36][37][38][39], four studies conducted in South Nations, Nationalities and Peoples Regional state (SNNPR) [5,29,40,41], two articles reported from Tigray regional state [16,21], one study reported from Harari regional state [19] and one study was conducted in Oromia region, Afar region and Dire Dawa city administration [42] (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The absence of publication bias was declared using Egger's test statistics with a p-value of 0.31 (Fig 4). The association between CD4+ T-cell counts <200cells/μl and intestinal parasitic infection among HIV/AIDS patients was computed using six studies [5,18,19,37,39,45]. The findings of this meta-analysis showed that HIV/AIDS patients with CD4+ T-cell count <200cells/μl https://doi.org/10.1371/journal.pone.0244887.g004…”
Section: Plos Onementioning
confidence: 99%